Consulting report - Municipality of Surco: ensuring the proper regulation and formalization of commercial, industrial, and service-based - Rugh, Leah Zeh (2024)
This research shows a solution to address the issue of labor informality in Santiago de Surco, Peru. The problem of informality affects over 80% of the economically active population in Santiago de Surco and thereby limits their access to social services, healthcare, and financial resources. Using a series of sprints and interviews, the researchers collected both qualitative and quantitative data, which shows that informal workers often lack knowledge about how to transition to formal employment. Many of these workers prefer to access information anonymously, such as through digital platforms or anonymous meetings. Through their research, the team identified TikTok advertisements as the most effective medium for reaching informal workers in Surco. The platform's popularity of the targeted and mostly affected age group in Peru favors this solution. By using TikTok advertisements, the project wants to raise awareness about the benefits of formal employment, such as healthcare, pensions, and access to formal financial services. The solution also includes community events to educate further and engage informal workers and their shift towards formality. The business model proposed by the researchers is also scalable. By making unpleasant information easily accessible through TikTok and local events, the solution helps to reduce barriers to formal employment. Since the economic growth of a country is strongly intertwined with the taxes gathered, this project is also improving the overall well-being of the community. The model's financial sustainability is supported by government subsidies and sponsorships, while its scalability allows it to be replicated in other districts, regions and countries beyond Peru facing similar challenges. This study highlights the potential of digital platforms like TikTok in addressing social issues and provides a roadmap to combat informality throughout Peru.